Recycling and ecotoxicity of flax/PLA composites: Influence of seawater aging - P. Davies; M. Le Gall; Z. Niu; A.I. Catarino; Y. De Witte; G. Everaert; H. Dhakal; C.H. Park; E. Demeyer (Composites Part C: Open Access, 2023)
Poly(lactic acid) is finding increasing applications as it is a bio-sourced compostable thermoplastic. Its properties can be improved by adding flax fibres, which are also compostable. The possibility to recycle the composite after service is attractive because it reduces waste in landfills, is a cost-effective measure to reduce the need for raw materials and extends the life span of composites. However, few reports are available to verify how recycling affects properties of flax-PLA composites. In addition, if these recycled materials are to be used in marine applications, it is important to investigate whether they will be adversely affected by seawater compared to virgin materials, as well as to investigate the toxicity of these materials for marine organisms. The goal of this work was to address these three points, i.e., to assess whether recycling and posterior environmental weathering (seawater exposure) changes the flax-PLA composite properties, and to assess these materials’ toxicity for biota (a benthic copepod species, Nitokra spinipes). First, our results indicate that recycling up to four times hardly affects the composite properties. However, immersion in seawater at 40 °C for up to nine months reduces tensile strength of both virgin and recycled composite by up to 60%. Finally, the ecotoxicity evaluation indicated that neither leachates from PLA nor from Flax-PLA induce immobilization of N. spinipes, nor were any immobilization effects induced by leachates resulting from materials aged for two months in seawater. These results will contribute to assessing the sustainability of future bio-based polymer applications.